George Bernard Shaw and the Malvern Festival - Ananisarab, Soudabeh (2017)
The Malvern Festival was established by Sir Barry Jackson in association with the lessee of the Malvern Theatre, Roy Limbert, in 1929. The Festival continued for ten seasons as an annual event until the outbreak of World War II in 1939, and then returned for one final season in 1949. The Festival was initially dedicated to the works of George Bernard Shaw with the repertoire of the first season wholly composed of the plays of this playwright. While during its twelve seasons the Festival fluctuated in the extent of its association with Shaw, in total the Festival presented two world premieres of Shaw’s plays and four British premieres. Furthermore, in addition to its dramatic productions, the Festival also featured other activities such as talks and exhibitions and attracted an impressive list of visitors and speakers including Allardyce Nicoll and Gabriel Pascal as well as performers such as Cedric Hardwicke and Stephen Murray. This thesis explores the development of the Malvern Festival, an event which has thus far given rise to scant academic scholarship. I argue that rediscovering the Malvern Festival has the potential to reorientate common critical understanding of early twentieth-century English theatre and its key locations. While much of the British theatre scholarship of this period has been concerned with drama in the capital, this study of Malvern demonstrates that regional theatres at this time had the capability of offering experimental drama which often failed to attract the attention of theatre managers in London. As the high prices of rent in the metropolis limited the financial risk accepted by many theatre managers in the early twentieth century, individuals such as Shaw and Jackson amongst others turned their attention away from London to the regions for new opportunities in staging a more experimental repertoire. This study of the Malvern Festival demonstrates that while Jackson and Shaw initially considered the Festival as the solution to their troubles with playhouses in London’s West End, the Festival soon became entangled with those familiar debates of venue and repertoire, and ultimately failed after twelve seasons. In the organisation of the Festival, there were a number of damaging contradictions, some of which were also evident in the ventures preceding the Festival such as the movement for building a National Theatre in England and the Vedrenne-Barker seasons at the Court Theatre. The Festival had simultaneous links with both the non-metropolitan, as a result of its location in Malvern, and the urban, through its target audience of the metropolitan elite. Thus while the Festival was held in Malvern, as a result of Jackson’s guiding philosophy much of the local population in Malvern were excluded from the activities included in the Festival. Additionally, the identity of the Festival was intertwined with both a sense of nostalgia for the past and an outlook towards the future. While Jackson emphasised less well-known classics in the repertoire of the Festival, he also flew critics into Malvern, and Limbert extended the activities of the Festival by presenting modern talkies. Other contradictions included Jackson’s pursuit of critical praise for the Festival’s productions and his desire to experiment away from theatrical norms, in addition to the lack of certainty surrounding the focus of the Festival which fluctuated between an emphasis on a star playwright, Shaw, and Jackson’s aim to celebrate the literary canon. Moreover, some of these clashes were then exacerbated by the Shavian drama performed as part of the Festival. It was the difficulties in reconciling such contradictions which resulted in the Festival’s failure to remain as an annual event. However, in this thesis I argue that regardless of the Festival’s lack of financial and popular success, the Malvern Festival allowed Shaw the creative space to write some of his most experimental work, which was then explored in production as part of the Festival on the stage of the Malvern Theatre.